A revision of the ant genus Octostruma Forel 1912 (Hymenoptera, Formicidae) - Longino, John T. (Zootaxa, 2013)
The ant genus Octostruma is restricted to the Neotropics, where it is an inhabitant of forest leaf litter and soil. The genus is reviewed, with an emphasis on the fauna of the MesoAmerican corridor. A total of 34 species are recognized, of which 19 are described as new. A key to species is provided, and the following new species are described: O. ascrobicula Longino, sp. nov., O. ascrobis Longino, sp. nov., O. convallis Longino, sp. nov., O. convallisur Longino, sp. nov., O. cyrtinotum Longino, sp. nov., O. excertirugis Longino, sp. nov., O. gymnogon Longino, sp. nov., O. gymnosoma Longino, sp. nov., O. leptoceps Longino, sp. nov., O. limbifrons Longino, sp. nov., O. megabalzani Longino, sp. nov., O. montanis Longino, sp. nov., O. obtusidens Longino, sp. nov., O. pexidorsum Longino, sp. nov., O. planities Longino, sp. nov., O. schusteri Longino, sp. nov., O. triquetrilabrum Longino, sp. nov., O. triangulabrum Longino, sp. nov., and O. trithrix Longino, sp. nov. Octostruma lutzi (Wheeler) and O. amrishi (Makhan) are removed from synonymy with O. balzani (Emery). Queens are newly associated with workers for O. amrishi (Makhan), O. rugiferoides Brown & Kempf, and O. wheeleri (Mann).